KURIKULUM MERDEKA BELAJAR DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ALIRAN PROGRESSIVISME - Sinta Wahyuni; Muhammad Zaim; Harris Effendi Thahar (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
This article aims to discuss the views of the progressivism school of philosophy towards the Independent Curriculum. The method used is a literature study with a hermeneutic approach to explain the reality that occurs through elements of interpretation and description. The concept of independent learning is in accordance with the educational philosophy of progressivism. Both emphasize the values of independence and freedom, and present a new perspective on the orientation of education in Indonesia. In practice, this creates a natural learning space and allows children to grow and develop according to their interests and talents. The goal of forming individuals with character can be realized, making education high-quality and providing tangible benefits for students in facing current developments.